2014
DOI: 10.1007/s40618-014-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic defects of the CYP21A2 gene in girls with premature adrenarche

Abstract: In girls with PA, the frequency of the underlying CYP21A2 genetic defects is similar to that observed in other populations. The carrier status is likely a contributing factor in the genotype-phenotype correlation in NC-CAH. However, polymorphisms and other genes may be implicated in the clinical manifestation of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Additionally, 3 children belonging to the SV group exhibited GnRH independent precocious puberty. At this time, more than 200 mutations in the CYP21A2 gene have been reported in numerous studies and there is a good concordance between the clinical phenotype and the patient genotypic findings [13,16,17,21,[37][38][39][40]. The genetic population profile of CAH and endocrinopathies in the Cypriot population is characterized by low consanguinity rates and by similarities to what is observed regarding these disorders in the Eastern Mediterranean countries [41,42].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, 3 children belonging to the SV group exhibited GnRH independent precocious puberty. At this time, more than 200 mutations in the CYP21A2 gene have been reported in numerous studies and there is a good concordance between the clinical phenotype and the patient genotypic findings [13,16,17,21,[37][38][39][40]. The genetic population profile of CAH and endocrinopathies in the Cypriot population is characterized by low consanguinity rates and by similarities to what is observed regarding these disorders in the Eastern Mediterranean countries [41,42].…”
Section: Discussionmentioning
confidence: 64%
“…Since 2007 our group has extensively studied the genetic implication of CYP21A2 in Cypriot patients with CAH. These included the true carrier frequency in the general population of Cyprus [10], the genotype-phenotype association with the various forms of CAH [14][15][16][17][18], the impact of heterozygosity in female patients with hyperandrogenemia [19,20], and the implication of variants in the untranslated 5′UTR region of the CYP21A2 gene [21]. In the present update, we present the molecular genetic features of the disease in patients of Cypriot descent over the last 11 years.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in the Mediterranean Basin, including research from our group, have confirmed as the most predominant genetic defects, the mutations IVS2-13A/C>G, p.Gln318 ∗ , p.Val281Leu, and c.329_336del (8bpdelE3) [12, 13, 33, 34]. Compared to normal female individuals, female carriers for 21-OHD frequently demonstrate an increased secretion of the 21-OH precursors 17-hydroxyprogesterone (17-OHP) and progesterone (P4) [3543] and lower levels of 11-deoxycorticosterone [37] as expected.…”
Section: Introductionmentioning
confidence: 87%
“…The symptoms at presentation are often indistinguishable from adrenarche, so that the diagnosis requires investigations. Studies in children with premature adrenarche have shown that 4-25% were diagnosed with CAH (31,32). Genetic investigations in a cohort of 59 individuals with androgen symptoms showed that 12 had NCAH, 19 were carriers and 18 were heterozygous for a polymorphism previously discussed with regard to causing increased androgen production (32).…”
Section: Clinical Presentationmentioning
confidence: 99%